(untitled) (Current Problems in Rail Vehicles, 2021)
Proof of safety of rolling stock against derailment is performed according to the standard EN 14363. There are three possible methods described in the standard. The Test Centre of VÚKV performs the tests according to the methods 2 and 3. For these tests, VÚKV has been continuously improving measuring equipment and a test rig. In the years 2015–2018, a project focused on the safety against derailment of freight cars was realized with the aim to develop and build a test rig of the second generation.